Kidney Histopathology of Gallus gallus domesticus Infected by E. coli in Denpasar, Bali - Andayani, Ni Kadek Prederika Sari; Setyawati, Iriani; Joni, Martin (Advances in Tropical Biodiversity and Environmental Sciences; Vol 2 No 1 (2018): ATBESDO - 10.24843/ATBES.2018.v02.i01.p04, 2018)
One of the diseases that attacks poultry especially laying hens ( Gallus gallus domesticus ) is colibacillosis, a disease caused by E scherichia coli . E. coli is a bacterium that has opportunistic properties, which is normally present in the digestive tract in a controlled amount, but when the condition of the chicken decreases, it can develop into pathogens. Kidneys are organs that are vulnerable to substances that are toxic and are also susceptible to bacterial infections. This study aimed to determine the histological structure of kidneys of laying hens ( Gallus gallus domesticus ) who died due to the infection of E. coli . The research was conducted at a Pathology Laboratory (BBVet), Denpasar. The hen’s kidneys were processed with the paraffin method and Hematoxylin-Eosin staining. Cell damage that occurs is observed by using the Image Raster application. The data obtained were analyzed with the scoring method. Renal histopathology parameters can be seen in the form of degeneration, necrosis, congestion, and inflammatory cell infiltration. The results obtained cell damages namely 46% of degeneration, 60% of necrosis, 44% of congestion and 76% of inflammatory cell infiltration.